JURIDICAL ANALYSIS OF THE CRIME OF ABORTION (STUDY OF DECISION NUMBER 40/PID.B/2020/PNWNO) - Yulifa, Windy Ratna; Santoso, Aris Prio agus; Aryono, Aryono (Khairun Law Journal, 2023)
This study aims to find out the judge's considerations in decision Number 40/Pid.B/2020/PN Wno and to find out the decision in case Number 40/Pid.B/2020/PN Wno in terms of positive law in Indonesia. The type of research used in this study is normative legal research or library research with 3 approaches, namely the statutory approach, the case approach and the conceptual approach. The results of this study indicate that the basis for the judge's considerations in imposing a sentence on the case referred to in the judge's decision Number 40/Pid.B/2020/PN Wno is juridical in nature consisting of the public prosecutor's indictment, witness testimony, defendant's statement, evidence, and Apart from that, the articles in the criminal code are non-juridical in nature, namely the reason for the defendant's actions and the consequences of the defendant's actions. That the crime of abortion has violated the provisions of Article 346 of the Criminal Code, this can be seen because the elements in accordance with that article have been fulfilled. Because of the above considerations, the judge decided that the defendant was found guilty so that the defendant had to serve a prison sentence of 1 year and 10 months.